Going underwater: multiple origins and functional morphology of piercing-sucking feeding and tracheal system adaptations in water scavenger beetle larvae (Coleoptera: Hydrophiloidea). Issue 1 (27th November 2020) - Rodriguez, Georgina; Fikáček, Martin; Minoshima, Yȗsuke N; Archangelsky, Miguel; Torres, Patricia L M
Abstract: Larvae of water scavenger beetles (Coleoptera: Hydrophiloidea) are adapted to a wide variety of aquatic habitats, but little is known about functional and evolutionary aspects of these adaptations. We review the functional morphology and evolution of feeding strategies of larvae of the families Hydrophilidae and Epimetopidae based on a detailed scanning electron microscope (SEM) analysis, analysis of video records of feeding behaviour and observations of living larvae. There are two main types of feeding mechanisms: chewing and piercing-sucking. The character mapping using the latest phylogenetic hypothesis for Hydrophiloidea infers the chewing system as the ancestral condition. The piercing-sucking mechanism evolved at least four times independently: once in Epimetopidae ( Epimetopus ) and three times in Hydrophilidae (Berosini: Berosus + Hemiosus ; Laccobiini: Laccobius group; Hydrobiusini: Hybogralius ). The piercing-sucking apparatus allows underwater extra-oral digestion and decreases the dependence of larvae on an aerial environment. A detailed study of the tracheal morphology of the piercing-sucking lineages reveals four independent origins of the apneustic respiratory system, all of them nested within lineages with piercing-sucking mouthparts. We conclude that piercing-sucking mouthparts represent a key innovation, which allows for the subsequent adaptation of the tracheal system, influences the diversification dynamics of the lineages and allows the shift to new adaptive zones.